A review of ammonia removal using a biofilm-based reactor and its challenges. (1st August 2022) - Zulkifli, Maryam; Abu Hasan, Hassimi; Sheikh Abdullah, Siti Rozaimah; Muhamad, Mohd Hafizuddin
Abstract: Extensive growth of industries leads to uncontrolled ammonia releases to environment. This can result in significant degradation of the aquatic ecology as well as significant health concerns for humans. Knowing the mechanism of ammonia elimination is the simplest approach to comprehending it. Ammonia has been commonly converted to less hazardous substances either in the form of nitrate or nitrogen gas. Ammonia has been converted into nitrite by ammonia-oxidizing bacteria and further reduced to nitrate by nitrite-oxidizing bacteria in aerobic conditions. Denitrification takes place in an anoxic phase and nitrate is converted into nitrogen gas. It is challenging to remove ammonia by employing technologies that do not incur particularly high costs. Thus, this review paper is focused on biofilm reactors that utilize the nitrification process. Many research publications and patents on biofilm wastewater treatment have been published. However, only a tiny percentage of these projects are for full-scale applications, and the majority of the work was completed within the last few decades. The physicochemical approaches such as ammonia adsorption, coagulation-flocculation, and membrane separation, as well as conventional biological treatments including activated sludge, microalgae, and bacteria biofilm, are briefly addressed in this review paper. The effectiveness of biofilm reactors in removing ammonia was compared, and the microbes that effectively remove ammonia were thoroughly discussed. Overall, biofilm reactors can remove up to 99.7% ammonia from streams with a concentration in range of 16–900 mg/L. As many challenges were identified for ammonia removal using biofilm at a commercial scale, this study offers future perspectives on how to address the most pressing biofilm issues. This review may also improve our understanding of biofilm technologies for the removal of ammonia as well as polishing unit in wastewater treatment plants for the water reuse and recycling, supporting the circular economy concept. Graphical abstract: Image 1 Highlights: This review discusses the biofilm reactors technologies used to remove ammonia from wastewater. Comparison of various types of biofilm reactors in removing ammonia was conducted. Biofilm reactors' limitations in ammonia removal were discussed, as well as their potential future path.